Wild-type but not Alzheimer-mutant amyloid precursor protein confers resistance against p53-mediated apoptosis - Xu, Xiao (The National Academy of Sciences, 1999)
Amyloid precursor proteins (APPs) are expressed in multiple organs and cell types in diverse species. Their conservation across species and high abundance in brain and the association of various APP missense mutations with autosomal dominant forms of familial Alzheimer’s disease (FAD) suggest important roles for APP in the central nervous system. However, the basic functions of APP in the central nervous system remain largely unknown. To assess potential effects of APP on neuronal death and survival, we transfected APP-deficient rat neuroblastoma cells (B103) with DNA constructs encoding wild-type or FAD-mutant human APP. Wild-type, but not FAD-mutant, APP effectively protected cells against apoptosis induced by ultraviolet irradiation, staurosporine, or p53. Wild-type APP also strongly inhibited p53 DNA-binding activity and p53-mediated gene transactivation, whereas FAD-mutant APP did not. We conclude that APP protects neuronal cells against apoptosis by controlling p53 activation at the post-translational level. Disruption of this function by mutations or alterations in APP processing could enhance neuronal vulnerability to secondary insults and contribute to neuronal degeneration.